2016
DOI: 10.1002/jmor.20573
|View full text |Cite
|
Sign up to set email alerts
|

Crabs grab strongly depending on mechanical advantages of pinching and disarticulation of chela

Abstract: A small morphological variation of an organ may cause a major change of its function in animal evolution. The function of decapod chela varies considerably among taxa, between sex, and even within an individual, but also retains a simple mechanism of motion. Therefore, the decapod chela is a suitable structure to study the evolutionary process of functional diversifications, although the relationship of form and function is inadequately understood, yet. We estimated the mechanical advantages of pinching and pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 53 publications
1
10
0
Order By: Relevance
“…The MA is a straightforward biomechanical metric which in a biological context was first introduced for vertebrates (Westneat 1995(Westneat , 2004 and was used since in many studies on vertebrate and arthropod jaw mechanics (Cooper and Westneat 2009;Sakamoto 2010;Habegger et al 2011;Dumont et al 2014;Senawi et al 2015;Cox and Baverstock 2015;Weihmann et al 2015b;Fujiwara and Kawai 2016;Blanke et al 2017a;Fabre et al 2017;Olsen 2017). The MA is defined as the inlever to outlever ratio.…”
Section: The Mechanical Advantage (Ma) As a Performance Metric For Inmentioning
confidence: 99%
“…The MA is a straightforward biomechanical metric which in a biological context was first introduced for vertebrates (Westneat 1995(Westneat , 2004 and was used since in many studies on vertebrate and arthropod jaw mechanics (Cooper and Westneat 2009;Sakamoto 2010;Habegger et al 2011;Dumont et al 2014;Senawi et al 2015;Cox and Baverstock 2015;Weihmann et al 2015b;Fujiwara and Kawai 2016;Blanke et al 2017a;Fabre et al 2017;Olsen 2017). The MA is defined as the inlever to outlever ratio.…”
Section: The Mechanical Advantage (Ma) As a Performance Metric For Inmentioning
confidence: 99%
“…*See Supplemental Results (Methods S1) for an explanation of claw-face viewing perspectives. finger (dactyl) purely pivots about a single axis defined by two articulation points on the propodus (Figures 1A-1A'') [18][19][20]. Muscles attached to opposite sides of the pivot open and close the claw, respectively.…”
Section: Comparative Morphology and Evolutionary History Of Shrimp CLmentioning
confidence: 99%
“…latro possesses a remarkable strength with a reported lifting force of up to 28 kg [8]. However, no previous study has reported the actual pinching force of this species, although a morphological study on crustaceans suggested that, among decapod crustaceans, the chelae of the coconut crab could generate the strongest pinching force [9]. In the present study, we aimed to (i) determine the pinching force of the wild coconut crab from measurement in situ and (ii) clarify how these animals acquired their mighty claw, using morphometric and ecological data.…”
Section: Introductionmentioning
confidence: 99%